Pengembangan Model Kewirausahaan SMK Melalui Koperasi Sekolah: Development of the Vocational Entrepreneurship Model through School Cooperatives - Nurbudiyani, Iin (Anterior Jurnal, 2013)
Entrepreneurship has important roles to play in a nation. Student should be equipped with academic capabilities and practical skills as well as entrepreneurial values and attitudes for future challenges of life. Therefore, a vocational education is strategic to develop through an entrepreneurship model. Purposes of this study are to find out the conditions of school cooperative, models applied to develop learning process for enhancing entrepreneurial attitudes among students, and whether or not the development of learning on the base of school cooperative can enhance the entrepreneurial attitudes among the students of Vocational Schools. The study is conducted by using a research and development method. Data used are quantitative data, such as the assessment scores of attitude tests. The data are supported by qualitative data, such as comment, critique, and recommendation for improvement from material and education experts, of product development. The data are collected using instruments of attitude test, observation, interview and questionnaires. The collected data are analyzed by using a path analysis technique.